Seasonal Forestry Archetype - Maryhori Quispe Castillo (ARQ)
The Seasonal Forestry Archetype proposes an alternative, community-oriented approach to forestry in Ucayali, integrating wood processing plants with local communities. Designed for the kakataibo ethnic group in Yamino, the model embraces the Amazonian worldview, emphasizing “spatial instability” and cultural specificity. By connecting productive spaces with the forest, this mobile project aims to promote community autonomy, thus improving their quality of life.